Islamic Law as A Cultural and Social Phenomenon - Risma, Risma; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study explores the concept of Islamic law, culture, and social dynamics through a sociological approach. Islamic law is understood as a legal system derived from divine revelation rather than human construction, thus carrying strong spiritual and transcendental dimensions. Its implementation aims to promote the welfare of humanity as a whole, both in this world and in the hereafter. Culture, according to Ali Ahmad Madkur, represents the manifestation of divine values embedded in society; therefore, in Islam, culture cannot be separated from the principles of tawhid. The discussion also highlights the reciprocal relationship between law and society. Sociology, as the study of social life, helps to analyze patterns of social change and their impact on legal systems. In the modern context, social transformation often occurs more rapidly than legal reform, requiring law to adapt accordingly. This creates unique challenges for Islamic law to remain relevant in the face of changing times without compromising its foundational principles. Through mechanisms such as ijtihad, qiyas, and the concept of maslahah, Islamic law demonstrates the ability to respond to social changes with flexibility while remaining firmly rooted in the values of shari‘a. The study concludes that Islamic law functions not only as an instrument of adaptation but also as a guiding force for social transformation, balancing divine injunctions with the needs of contemporary society. Hence, Islamic law plays a vital role in maintaining harmony between religious teachings and evolving social realities.